1999
DOI: 10.1007/s000240050291
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Velocities and Anisotropy of the Lower Continental Crust: A Review

Abstract: Seismic anisotropy is often neglected in seismic studies of the earth's crust. Since anisotropy is a common property of many typically deep crustal rocks, its potential contribution to solving questions of the deep crust is evaluated. The anisotropic seismic velocities obtained from laboratory measurements can be verified by computations based on the elastic constants and on numerical data pertaining to the texture of rock-forming minerals. For typical lower crustal rocks the influence of layering is significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 52 publications
3
86
0
Order By: Relevance
“…However, laboratory measurements as well as borehole seismic investigations have shown that these assumptions are a reasonable approximation for many anisotropic crustal rock in which the elastic properties of mineral assemblages get averaged within the foliation plane (see e.g. Rabbel et al 1998;Weiss et al 1999;Rabbel et al 2004;Okaya et al 2004). Therefore, we do not see this assumption as a major restriction.…”
Section: O D E L S Y S T E M At I Cmentioning
confidence: 94%
“…However, laboratory measurements as well as borehole seismic investigations have shown that these assumptions are a reasonable approximation for many anisotropic crustal rock in which the elastic properties of mineral assemblages get averaged within the foliation plane (see e.g. Rabbel et al 1998;Weiss et al 1999;Rabbel et al 2004;Okaya et al 2004). Therefore, we do not see this assumption as a major restriction.…”
Section: O D E L S Y S T E M At I Cmentioning
confidence: 94%
“…Laboratory measurements and theoretical calculations have established that at middle to lower crustal depths seismic anisotropy can be a signature of ductile deformation and is primarily attributed to the lattice-preferred orientations (LPO) of major rock-forming minerals, in particular micas and amphiboles (Mainprice and Nicolas, 1989;Weiss et al, 1999;Nishizawa and Yoshitno, 2001). Most of these minerals typically show hexagonal symmetry with the orientation of axis of symmetry depending on strain orientation (Meissner et al, 2006).…”
Section: Bohai Bay Basin and Taihang Mountains (Eastern And Central Ncc)mentioning
confidence: 98%
“…Consequently, when it is highly refl ective, it is modeled as intercalated lenses of high-and lowvelocity material that represent these lithologies (Carbonell and Smithson, 1991;Mooney and Meissner, 1992;Weiss et al, 1999;Carbonell et al, 2002;Giese, 2005). In detail, however, the character of the Moho transition may be the result of a wide range of possible structures, mineralogical and geochemical compositions, thermal evolutions, and formational processes (Hale and Thompson, 1982).…”
Section: Introductionmentioning
confidence: 99%